ONLINE PURCHASE DECISIONS: ANALYSIS E-SERVICE QUALITY AND INFORMATION QUALITY IN TOKOPEDIA - La Ode Sugianto; Titis Purwaningrum; Siti Chamidah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of E-service quality and information quality on online consumer purchasing decisions at Tokopedia, Madiun Regency. The type of research used is descriptive quantitative research. This study uses the Non Probability Sampling technique using the Accidental Sampling approach. The analysis technique uses statistical analysis, statistical test with linear regression test, determination test and t test and f test. The results of this study indicate that the E-service quality variable has a significant effect on online purchasing decisions at Tokopedia, Madiun Regency. The information quality variable has a significant effect on online purchasing decisions at Tokopedia, Madiun Regency. E-service quality and information quality simultaneously have a significant effect on online purchasing decisions at Tokopedia, Madiun Regency. The value of the R Square when converted into percent is 58.7%. This percentage explains that the variables of e-service quality and information quality are able to influence the variables of consumer online purchasing decisions at Tokopedia, Madiun Regency by 58.7% and the rest is influenced by other variables outside the study, which is 41.3%, so there is still a chance variables outside the study that affect purchasing decisions.